Association between Fruit and Vegetable Intakes and Mental Health in the Australian Diabetes Obesity and Lifestyle Cohort - Rees, J.; Bagatini, S.R.; Lo, J.; Hodgson, J.M.; Christophersen, Claus; Daly, R.M.; Magliano, D.J.; Shaw, J.E.; Sim, M.; Bondonno, C.P.; Blekkenhorst, L.C.; Dickson, J.M.; et al. (MDPI, 2021)
Increasing prevalence of mental health disorders within the Australian population is a serious public health issue. Adequate intake of fruits and vegetables (FV), dietary fibre (DF) and resistant starch (RS) is associated with better mental and physical health. Few longitudinal studies exist exploring the temporal relationship. Using a validated food frequency questionnaire, we examined baseline FV intakes of 5845 Australian adults from the AusDiab study and estimated food group-derived DF and RS using data from the literature. Perceived mental health was assessed at baseline and 5 year follow up using SF-36 mental component summary scores (MCS). We conducted baseline cross-sectional analysis and prospective analysis of baseline dietary intake with perceived mental health at 5 years. Higher baseline FV and FV-derived DF and RS intakes were associated with better 5 year MCS (p < 0.001). A higher FV intake (754 g/d vs. 251 g/d, Q4 vs. Q1) at baseline had 41% lower odds (OR = 0.59: 95% CI 0.46–0.75) of MCS below population average (<47) at 5 year follow up. Findings were similar for FV-derived DF and RS. An inverse association was observed with discretionary food-derived DF and RS. This demonstrates the association between higher intakes of FV and FV-derived DF and RS with better 5 year mental health outcomes. Further RCTs are necessary to understand mechanisms that underlie this association including elucidation of causal effects.